WRITING SKILLS IN DESCRIPTIVE TEXT THROUGH PICTURE SERIES: THE MOTIVATION AND SELF-CONFIDENCE - Lola Laila; Rasi Yugafiati (PROJECT (Professional Journal of English Education), 2023)
This research was conducted to determine the motivation of students in writing descriptive texts. Students' writing abilities were related to motivation and self-confidence. The type of research was pre-experimental quantitative research with the One-Group model and pretest-posttest instruments. The data collection used three stages. First, the researcher read students’ worksheets. Second, the researcher identified the students' worksheets. Third, the researcher evaluated the results of students’ worksheets. The population used was the seventh-grade students of SMP Islam Sulaimaniyyah semester 2. There were thirty-five students. There are fifteen girls and twenty boys. From the results of the SPPS Statistics 25 calculation, sig. (2-tailed) of 0,000 which means lower than sig. 0.05. Ho hypothesis was rejected and Ha hypothesis was accepted, it was concluded that the picture series was influencing and increasing students' motivation in writing descriptive texts with the final result of 9.93% while the initial results reached 5.65%. The impact of the research trains students’ motoric skills in vocabulary mastery, and students’ activities in the class, and attracts students’ interest in writing through picture series with a fun learning atmosphere.